Transfer of Dorsoventral and Terminal Information from the Ovary to the Embryo by a Common Group of Eggshell Proteins in Drosophila - Mineo, Alessandro (Genetics, 2017)
The Drosophila eggshell is an extracellular matrix that confers protection to the egg and also plays a role in transferring positional information from the ovary to pattern the embryo. Among the constituents of the Drosophila eggshell, Nasrat, Polehole, and Closca form a group of proteins related by sequence, secreted by the oocyte, and mutually required for their incorporation into the eggshell. Besides their role in eggshell integrity, Nasrat, Polehole, and Closca are also required for embryonic terminal patterning by anchoring or stabilizing Torso-like at the eggshell. Here, we show that they are also required for dorsoventral patterning, thereby unveiling that the dorsoventral and terminal systems, hitherto considered independent, share a common extracellular step. Furthermore, we show that Nasrat, Polehole, and Closca are required for proper Nudel activity, a protease acting both in embryonic dorsoventral patterning and eggshell integrity, thus providing a means to account for the role of Nasrat, Polehole, and Closca. We propose that a Nasrat/Polehole/Closca complex acts as a multifunctional hub to anchor various proteins synthesized at oogenesis, ensuring their spatial and temporal restricted function.